A new paleofloristic assemblage from the Cuyana Basin (Agua de los Pajaritos depocenter), Argentina and its paleobiogeographic and paleoenvironmental implications - Drovandi, Juan Martín (2020)
In this study, we examined the first paleofloristic record for the Monina Formation, Middle Triassic, Agua de los Pajaritos depocenter, Cuyana Basin, San Juan Province, Argentina. The paleoflora includes representatives of Isoetales, Peltaspermales, and Coniferales in addition to some unidentified taxa classified as incertae sedis. The species determined, described, and compared were: Lepacyclotes sp.; Matatiella cf. roseta, Anderson and Anderson2003; Scytophyllum sp.; Cf. Rissikianthus; Protocircoporoxylon sp.; Cordaicarpus sp.; and Acevedoa cf. rastroensis (Arce and Lutz) Arce and Lutz 2014. In addition, a model is proposed to determine paleofloristic associations as well as reconstruction of the paleoenvironment based on the depositional architecture and the preservational mode of the paleofloristic remains.